Experts' view on the role of oestrogens in combined oral contraceptives: emphasis on oestetrol (E4) - Creinin, M. D.; Cagnacci, A.; Spaczyński, R. Z.; Stute, P.; Chabbert-Buffet, N.; Korver, T.; Simoncini, T. (Frontiers in Global Women's Health, 2024)
Introduction: The evolution of contraception has been crucial for public health and reproductive well-being. Over the past 60 years, combined oral contraceptives (COCs) have remained an important part of the contraceptive landscape worldwide; continued development has worked toward maintaining efficacy and improving safety. Methods: Seven global experts convened to discuss the clinical relevance of the oestrogen in COCs, focusing on the impact of the new oestrogen, oestetrol (E4). Participants then commented through an online forum on the summary content and other participants' feedback. We prepared this report to describe the experts' views, their follow-up from the open forum and the evidence supporting their views. Results: Ethinylestradiol (EE) and estradiol (E2) affect receptors similarly whereas E4 has differential effects, especially in the liver and breast. Adequate oestrogen doses in COCs ensure regular bleeding and user acceptability. EE and E4 have longer half-lives than E2; accordingly, COCs with EE and E4 offer more predictable bleeding than those with E2. Oestrogen type and progestin influence VTE risk; E2 poses a lower risk than EE; although promising, E4/DRSP VTE risk is lacking population-based data. COCs alleviate menstrual symptoms, impact mental health, cognition, libido, skin, and bone health. Conclusion: Oestrogens play an important role in the contraceptive efficacy, bleeding patterns, and overall tolerability/safety of COCs. Recent studies exploring E4 combined with DRSP show promising results compared to traditional formulations, but more definitive conclusions await further research.